The effectiveness of foreign aid in Bolivia: Final report - Lykke E. Andersen; José Luis Evia (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2003)
During the last five years, Bolivia received more than US 3,000 million in foreign aid and more than US 3,500 million in Foreign Direct Investment (FDI). The country also received debt relief with a net present value of US 1,300 million and implemented a National Poverty Reduction Strategy. During the same period, however, the GDP growth rate fell from an average level of 4.7% between 1993 and 1998 to an average level of 1.7% between 1999 and 2002, relative and absolute poverty increased, and the fiscal deficit increased to 8.7% of GDP in 2002. These numbers suggest that neither foreign aid, nor debt relief, nor FDI has the capacity to increase growth rates and reduce poverty in Bolivia. This, however, is not necessarily true. It could be the case that without these positive shocks, the situation would have been even worse due to other negative shocks. The only way to separate the effects of different shocks is to use a Computable General Equilibrium (CGE) model, where the effects of changes in one variable can be analyzed while holding all other exogenous variables constant. The model used for this project contains a variety of sectors and household types which permits the analysis of aggregate effects on the GDP growth rate, the balance of payments, the fiscal deficit, etc, as well as distributional effects indicating who benefits and who is hurt by different policies. The distributional analysis is of particular importance when poverty is a main concern since aggregate GDP growth does not necessarily reduce poverty. Estimations by UDAPE indicate that the elasticities of poverty with respect to changes in GDP are extremely low in Bolivia: Only 0.3% in rural areas and 0.6% in urban areas[1]. This means that during the last decade, growth in Bolivia has clearly not been pro-poor, despite the stated emphasis on poverty reduction. During the period 1998-2002, Bolivia received on average 614 million in foreign aid per year. For the period 2003-2006, there are commitments implying that this amount will increase to 872 million per year, which means an increase in the level of annual foreign aid of 258 million. This report used the CGE model to simulate the effect of additional foreign donations of 258 million per year for four years, after which the level of aid returns to its “normal” level. Such a simulation allows us to see the effects of the initial expansion, the effect of the subsequent contraction, as well as the long run effects after the temporary increase in foreign aid.The effects of this extra aid will obviously depend on how the money is used. Applying the combination of public spending and public investment that we consider most likely, the simulations show an increase in the GDP growth rate of approximately 1 percentage point per year during the four years of extra aid, but when the extra aid disappears, the growth rates return to their normal levels. It is important to stress that public investment in the model is assumed to produce public goods, which increase the productivity of everybody. The extra aid has a corresponding positive effect on average incomes of the households for four years, but those who benefit most are skilled workers who are already among the richest in Bolivia, while the biggest and poorest group in Bolivia, the rural small-holders, are worse off every year during and after the extra aid, compared to the base scenario (without extra aid). This means that foreign aid, despite the very best intentions, tends to increase inequality and deepen poverty. This is not due to project failure at the micro level, but rather to adverse secondary effects at the macro level. It is perfectly possible that all aid projects are successful at the micro level, while the impacts at the macro level remain very close to zero. This paradox between the success of projects at the micro level and the lack of success at the macro level can be explained by the following arguments: First, aid projects distract resources away from other activities. Even when projects are 100% funded by foreign donations (the assumption used in the simulations), the project will use human resources which, in the absence of the project, could have been applied elsewhere. Since foreign aid projects usually skim the cream in terms of local human resources, this may imply a large social opportunity cost. This effect is particularly important in Bolivia, where the public sector (with the heavy support of foreign aid) is so attractive that few professionals are interested in working in the private, productive sector. And since this system appears to be relatively permanent, the new generations of students are demanding education that qualifies them to be politicians and bureaucrats, while few students are planning on working in the private sector, and much less create their own enterprises. Besides, not all aid projects are fully financed by donations, the majority of projects are financed by loans, and those that include a donation component, usually requires counterpart financing. This means that aid projects not only distract scarce human resources away from other activities, but also scarce financial resources. The second adverse macroeconomic effect arises through the real appreciation of the exchange rate that invariably follows from a large influx of dollars into the economy. This negatively affects most exporting sectors as their products become relatively more expensive on the international markets, and it negatively affects domestic producers of tradable goods as they have to compete with cheaper imports. The result is a reduction in the domestic production of tradable goods. Theoretically, the Central Bank could neutralize this effect by increasing its reserves of dollars or by paying off foreign debt, but this is unlikely to happen as most aid is tied to specific projects. The fact that the macroeconomic effects of foreign aid on monetary indicators tend to be small and temporary does not imply that foreign aid is useless. Many non-monetary indicators of well-being have increased substantially during the period, especially the indicators related to school enrollment, health, water, and sanitation. The Bolivian government is well aware of the asymmetry between progress in the provision of basic services and the lack of progress in the capacity of the population to increase its incomes: The real per capita income in Bolivia is practically the same as it was 50 years ago, despite the advances in education, health and basic services. The government is therefore changing the focus of its Poverty Reduction Strategy, laying more emphasis on the productive sectors. Fourteen sub-sectors with a high employment generation capacity have been selected for particular interventions in terms of infrastructure, market access, technical assistance, training, etc. Ten of these sub-sectors are part of modern agriculture, a sector whose expansion, according to our CGE analysis, would be beneficial not only because it raises average incomes, but also because it improves the income distribution. This is in contrast to the hydrocarbon sector and the mining sector, whose expansions tend to worsen the income distribution. Another sector whose expansion is highly desirable from a poverty reduction viewpoint, is the one producing consumer goods, usually through small and medium sized enterprises. The expansion of this sector would benefit the two big groups of poor households in Bolivia: the rural small-holders and the urban informals, and thus have a beneficial effect on both rural and urban poverty. In order to generate the largest and most sustainable impact possible of future foreign aid, it is recommended that donors and the government revise projects in three dimensions: First, they should check to which extent the projects create true public goods that increase the productivity of large groups of people, and to which extent they just generate short run activities which substitute for other, and possibly more sustainable, activities. The larger the public good component, the better the long run impact. Second, they should evaluate whether the projects help reduce the scarcity of skilled workers. It is the scarcity of skilled workers and the abundance of unskilled workers that generate high inequality in Bolivia, and projects which improve the quality of unskilled workers would tend to have a positive effect on the distribution of income in Bolivia and thus a beneficial effect on poverty. Third, they should check which sectors are likely to benefit or suffer from different projects, as the expansion of the sectors modern agriculture, coca, and consumer goods will have a much better impact on poverty than the expansion of mining, hydrocarbons, and formal services. It is often difficult to predict the impact of specific projects, and particularly difficult to assess how big the public good component of the project is. In order to learn from the past, it would be interesting to make a detailed retrospective analysis of past aid projects in Bolivia, evaluating which public goods have been created and what has been their impact on productivity. Specifically, donor agencies could provide a complete list of projects completed during the year 2000, and an independent team could analyze the project documentation and visit the project site some years after conclusion in order to evaluate the impact of the project. With a sample of 60-100 projects, it would be possible to make a statistical analysis, identifying what kind of projects would be most likely to generate not only positive impacts at the micro level but also at the macro level.
Keywords: 330; Foreign aid; growht; poverty; Bolivia; CGE modelling; Entwicklungshilfe; Armut; Armutspolitik; Bolivien